Improving Mobile Core Network Security with Honeynets. - Dimitriadis, C.K (IEEE Security and privacy : building confidence in a networked world)
Despite improved security, core network vulnerabilities continue to threaten third-generation (3G) mobile systems. This article offers a security assessment conducted in the packet-switched domain of a mobile operator's infrastructure. A honeynet architecture could help address 3G security.